Evaluating Digital Transformation Policy in Teacher Professional Allowance Services: Administrative Efficiency and Teacher-Conditions - Corry Vicoresita; Hayat; Rini Rahayu Kurniati (FOUNDASIA, 2025)
Digital transformation in education policy implementation is essential to improve efficiency, transparency, and accountability, particularly in the management of Teacher Professional Allowance (TPG) as a government policy instrument. This study aims to analyze the implementation of digital transformation within the Teacher Professional Allowance (TPG) policy at the Department of Education and Culture of Sidoarjo Regency and its impact on teachers' teaching performance. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that the digital transformation of the TPG policy has improved administrative efficiency, transparency, and accessibility for teachers. However, several challenges persist, including infrastructure limitations, lack of system integration, and disparities in digital competencies, indicating that the policy implementation has not been fully optimized. The implementation has positively impacted teacher professionalism, motivation, and teaching performance, although the impact remains uneven across different contexts. The study recommends strengthening policy integration, enhancing human resource capacity, and developing clear digital governance standards to improve the effectiveness of education policy implementation.